Puerarin Prevents Acute Liver Injury via Inhibiting Inflammatory Responses and ZEB2 Expression - Yang, Junfa; Wu, Maomao; Fang, Hui; Su, Yue; Zhang, Lingling; Zhou, Huan (Frontiers in Pharmacology, 2021)
Puerarin, an isoflavone component extracted from herb radix puerariae, is widely used in China in the treatment of immune diseases and inflammation. Previous studies have demonstrated that puerarin prevented acute lung injury by regulating inflammatory responses. However, the effect of puerarin on acute liver injury (ALI) was unclear. The purpose of this study was to explore the beneficial effects of puerarin when applied to ALI. We found that puerarin inhibited liver injury and inflammatory cell infiltration in lipopolysaccharide (LPS)/D-galactose (D-Gal)-induced acute liver failure and the liver pro-inflammatory cytokines interleukin (IL)-1β, IL-6, and tumor necrosis factor-alpha (TNF-`α) in liver tissues with ALI and LPS-induced L-02 cells but upregulated the expression level of zinc finger E-box-binding homeobox 2 (ZEB2). Significantly, the results of this study showed that the inhibition of liver pro-inflammatory cytokine (IL-1β, IL-6, and TNF-α) production in LPS-induced L-02 cells was caused by ZEB2 overexpression. However, knocking down ZEB2 promoted LPS-mediated secretion of liver pro-inflammatory cytokines in L-02 cells. Additional experiments showed that puerarin inhibited the activation of the NF-κB signaling pathway by elevating ZEB2 expression in L-02 cells. In summary, puerarin most likely prevented activation of the pro‑inflammatory factors and reduced LPS/D-Gal‑induced liver injury by enhancing the ZEB2 expression level and, consequently, blocking activation of the NF‑κB signaling pathway in the liver.